2019
DOI: 10.1038/s41467-019-11566-2
|View full text |Cite
|
Sign up to set email alerts
|

Photo-editable macromolecular information

Abstract: Light-induced alteration of macromolecular information plays a central role in biology and is known to influence health, aging and Darwinian evolution. Here, we report that light can also trigger sequence variations in abiotic information-containing polymers. Sequence-coded poly(phosphodiester)s were synthesized using four phosphoramidite monomers containing either photo-sensitive or photo-inert substituents. These monomers allow different sequence manipulations. For instance, using two light-cleavable monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 39 publications
0
56
0
1
Order By: Relevance
“…37 Yet, our group has reported very recently the sequence-directed photo-mutation of synthetic informational polymers. 38 Open challenges for polymer chemists. To attain polymer-based artificial Life (if attainable at all), major challenges lie ahead for polymer chemists.…”
mentioning
confidence: 99%
“…37 Yet, our group has reported very recently the sequence-directed photo-mutation of synthetic informational polymers. 38 Open challenges for polymer chemists. To attain polymer-based artificial Life (if attainable at all), major challenges lie ahead for polymer chemists.…”
mentioning
confidence: 99%
“…However, it is already possible to perform discrete monomer modifications in synthetic information‐containing macromolecules. For instance, our group has recently reported that light can be used as a simple trigger to induce molecular changes in sequence‐coded poly(phosphodiester)s . Such a concept is inspired by irradiation‐mediated mutagenesis and enables site‐directed mutations in synthetic polymers.…”
Section: Synthetic Chemistrymentioning
confidence: 99%
“…[ 10,17 ] To date, only a limited number of approaches using sequence‐defined macromolecules have been developed for the specific purpose of data encryption. [ 16,27,28 ] For instance, Lutz and co‐workers reported the use of sequence‐defined poly(alkoxyamine amide)s for the encoding and decoding of information, which can be read‐out via tandem mass spectrometric (MS) analysis. [ 27 ] Their study was completed by the total and uncontrolled erasing of the information using thermally induced degradation of the polymeric structure, which they claimed to be potentially easier to sequence than using biopolymers.…”
Section: Introductionmentioning
confidence: 99%